Green pathways for biomass transformation : A holistic evaluation of deep eutectic solvents (DESs) through life cycle and techno-economic assessment - Yiin, Chung Loong; Lai, Zhi Ying; Bridgid Chin, Lai Fui; Serene Lock, Sow Mun; Cheah, Kin Wai; Martin J., Taylor; Amthal, Al-Gailani; Ben W., Kolosz; Chan, Yi Herng (Elsevier Ltd., 2024)
The utilization of renewable biomass resources to manufacture biofuels, chemicals, and materials has garnered considerable attention. Deep eutectic solvents (DESs) have surfaced as a promising instrument within the realm of biomass conversion, owing to their distinctive attributes such as biodegradability, negligible toxicity, easier fabrication, liquid-phase stability and renewability as opposed to ionic liquids (ILs). Research into DESs, particularly those derived from natural sources, is expanding to advance affordable and sustainable biomass conversion. However, the bottlenecks of DES are its limited solubility for certain biomass constituents, cost and availability. To overcome these hurdles, ongoing research and technological innovations strive to tap into the complete potential of DESs in biomass conversion. This review underscores the importance of evaluating DESs' eco-friendly potential comprehensively, encompassing ecological, financial, and technological standpoints which aims to illuminate how DESs can effectively contribute to sustainable biomass utilization, fostering an environmentally conscious circular bio-based economy.